Cognitive predictors of parental behavior in abused mothers - Aguinaga Alvarez, Adolfo (2024)
The major objective of this study was to identify the rational behavior factors that predict parental behavior in 100 mothers who reported being abused by their partners and attended the Institute of Legal Medicine and Forensic Sciences in the city of Lima for evaluation. The instruments used to collect the information were the Rational Behavior Inventory and the Parental Behavior Inventory. Multiple regression analysis was applied using the stepwise method to identify the factors of rational behavior that predict parental behavior in the study sample. The findings show that the disapproval factor predicts hostile/coercive parental behavior with a positive correlation, while the degree of independence factor negatively predicts parental support/commitment behavior. Although the feeling of guilt factor does not play a predictive role, its positive correlation with hostile/coercive parental behavior is discussed. The findings are intended to contribute to the knowledge of mother-child interaction in contexts of partner violence and motivate appropriate decisions to face this problem.